Association of nucleated red blood cell count with mortality among neonatal intensive care unit patients - Sarah U. Morton; Kaitlyn Brettin; Henry A. Feldman; Kristen T. Leeman (Elsevier, 2020)
Background: Nucleated red blood cells (nRBCs) are associated with adverse outcomes for pediatric and adult intensive care patients. Methods: The association between nRBC count and mortality was examined in an observational cohort of patients admitted to the neonatal intensive care unit from December 2015-December 2018. Results: Among the 1059 patients with at least one nRBC count obtained, 45 infants (4.2%) experienced in-hospital mortality prior to NICU discharge, the primary outcome measured in this study. Infants with any nRBC count >0 had a significantly higher risk of mortality (5.3% [45/849] vs. 0% [0/351], p < 0.001 by Fisher exact), and time to mortality decreased with higher nRBC counts (Spearman correlation −0.59, p < 0.001). The association between nRBC count and mortality remained significant even when restricting only to infants who were older than 7 days at time of nRBC count. Conclusion: Among neonatal intensive care unit patients, including those >7 days old, nRBCs are associated with significantly elevated mortality risk. A prospective study to better characterize clinical co-variants is necessary to better establish the use of nRBCs as a predictor of mortality.